(3cJGH eG jSJYed aj UfGYI GdWH hjfJaY Hg hajeG dGjSJYeds - (3SdjeGf Hf MSGf GdCfOdSj CHh OGhO, GdeYQha HGHf oLrdoLd,J (B377 (3g` s
(3ChdgG (B:s
(3aef Pdc GdgdjdL GdCUaQ hgh ef GdCOhjI GdgfOjI hgh ai eRGLg GdZGdH Ydjg GdHQO hGdjGHS s
(3BNQgG (B:s
(3GdcQce gh YbjQ gfOi jSejg Cgd GdYQGb GdcQce hgh GdYQhb GdUaQ hgh CUhd UdHI JTHg GdRfLHjd JeJ ebGdg GHf LdLd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B123 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B258s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs